Correlation between blood levels of cadmium and lead and the expression of microRNA-21 in Egyptian bladder cancer patients. Issue 12 (December 2020) - Awadalla, Amira; Mortada, Wael I.; Abol-Enein, Hassan; Shokeir, Ahmed A.
Abstract: Objective: To investigate the relationship between blood levels of cadmium (Cd) and lead (Pb) and the expression of miRNA-21 among bladder cancer (BC) patients. Material and methods: The blood concentrations of Cd and Pb in 268 BC patients and 132 controls were determined by inductively coupled plasma optical emission spectrometry (ICP-OES). The blood concentrations of Cd and Pb were interpreted according to the type and stage of the carcinoma. The expression of miRNA-21 was assessed by quantitative reverse transcription polymerase chain reaction in cancerous and adjacent non-cancerous bladder tissues among the patient groups. Results: The blood concentrations of Cd and Pb were statistically elevated in BC patients compared to those of the controls. This elevation is more prevalent in groups with muscle-invasive bladder cancer (MIBC) than those with non-muscle invasive bladder cancer (NMIBC). Among the BC group, miRNA-21 was upregulated in cancerous tissues relative to adjacent non-cancerous tissues. Moreover, the expression was significantly higher in patients with MIBC compared to those with NMIBC. The expression of miRNA-21 in cancerous tissues was significantly associated with blood concentration of Cd and Pb among BC patients. Conclusion: There is a relationship between Cd and Pb body burden and the tissue expression of miRNA-21 among BC patients. This indicates the role of miRNA-21 in Cd and Pb induced BC. Abstract : Environmental pollution; Gene expression; Cancer research; Oncology; Toxicology; Clinical research; Cadmium; Lead; miRNA-21; Bladder cancer.